Ketamine-Based Anesthetic Protocols and Evoked Potential Monitoring: A Risk/Benefit Overview - Stoicea, Nicoleta; Versteeg, Gregory; Florescu, Diana; Joseph, Nicholas; Fiorda-Diaz, Juan; Navarrete, Víctor; Bergese, Sergio D. (Frontiers in Neuroscience, 2016)
Since its discovery, ketamine, a noncompetitive N-methyl D-aspartate (NMDA) receptor antagonist related to phencyclidine, has been linked to multiple adverse reactions sometimes described as “out of body” and “near death experiences”, including emergence phenomena, delusions, hallucinations, delirium, and confusion. Due to these effects, ketamine has been withdrawn from mainstream anesthetic use in adult patients. Evoked potentials (EPs) are utilized to monitor neural pathways during surgery, detect intraoperative stress or damage, detect and define the level of neural lesions, and define abnormalities. Unfortunately, many of the volatile anesthetics commonly used during spinal and neurologic procedures suppress EP amplitude and monitoring.. Ketamine has been found in several preclinical and clinical studies to actually increase EP amplitude and thus has been used as an analgesic adjunct in procedures where EP monitoring is critical. Once the gap in our knowledge of ketamine’s risks has been sufficiently addressed in animal models, informed clinical trials should be conducted in order to properly incorporate ketamine-based anesthetic regimens during EP-monitored neurosurgeries.